AKTIVASI KOGNITIF SISWA SMA KELAS XI MELALUI DESAIN PEMBELAJARAN CONSTRUCTING SCIENTIFIC EXPLANATIONS PADA MATERI SISTEM PERTAHANAN TUBUH - Nabilla Hadistia, - (2022)
Science learning currently requires students to be able to use their understanding in building scientific explanations with the characteristics of a more systematic, deeper, and more accurate explanation. In addition, the demands of basic competence on the material of the body's defense system require cognitive activation of students so that a thought process occurs in constructing a teaching material through scientific explanations. This study aims to analyze the cognitive activation of high school students in class XI through the learning design of constructing scientific explanations on the material of the body's defense system. The method used is an experiment with a one-shot case study research design. Assessment of cognitive activation was obtained through group and individual worksheets, as well as description tests from 30 high school students in class XI in one school in the city of Cimahi. The assessment refers to activities during learning from starting to present investigating activities, formulating how-why type questions, building initial causal stories, using authentic data/similar facts, and principles for revising initial causal stories, discussing enhanced causal stories, and applying knowledge. in new problem contexts/scenarios. In addition, students' responses during the learning process were investigated in this study. The results show that through this learning design there are different achievements of students' cognitive activation. From a total of 73% of students who at the time of building the initial causal story were at the basic level, it was reduced to 53% of students. The final total who were at the advanced level amounted to 27% of students. Students prefer to focus on a limited set of causes or just fill in the explanation with surface information. Students tend to simplify the cause-and-effect story about the phenomenon, either Covid-19 or chickenpox, so that they only report a single incident without explaining the cause.